RELEVANSI ANTARA KOMPETENSI MATA PELAJARAN PRODUKTIF DENGAN PEKERJAAN DALAM PELAKSANAAN PRAKTEK KERJA INDUSTRI SISWA PROGRAM KEAHLIAN TEKNIK KENDARAAN RINGAN SEKOLAH MENENGAH KEJURUAN MIGAS CEPU TAHUN AJARAN 2014/2015 - Nico Haylusi; Suparmin Suparmin (Universitas Sarjanawiyata Tamansiswa, 2015)
This research was aimed to know (1) The level of relevance between competence productive subjects given vocational Migas Cepu with the work of the student in the implementation of industry work practices. (2) The work of students obtained during the conduct of industrial work practices (3) The intensity of the work of the student in the implementation of industry work practices.Research was conducted in SMK Migas Cepu with research subjects TKR class XII students of the school year 2014/2015, amounting to 67 students. Data collection on subjects productive competence in a manner of documentation and data on student employment obtained using a questionnaire. The validity of items obtained by calculating the formula product moment. The analysis technique used is quantitative descriptive statistical analysis with percentages.Based on the analysis of data it can be concluded that: (1) the degree of relevance of competence subjects prakerin productive in the implementation of 91% (very relevant) with details of Vocational Competency Basic relevance to the work of 96% (very relevant), and the relevance of Vocational Competency by 87% (very relevant). (2) the work of the student in the implementation of industry work practices is the implementation of competency productive subjects with an average Vocational Competency Basic implementations of 3.3 (very high) and the implementation of Vocational Competency an average of 2.8 (low). (3) There are 6 very low intensity of work performed in the workshop students prakerin Non ATPM, and 4 very low intensity work done in the workshop students prakerin ATPM and Non ATPM.